Docking phenomenon and subsequent acetabular development after gradual reduction using overhead traction for developmental dysplasia of the hip over six months of age. (2021) - Kaneko, Hiroshi; Kitoh, Hiroshi; Kitamura, Akiko; Sawamura, Kenta; Hattori, Tadashi
Abstract: Purpose: This study aimed to explore the docking of the femoral head into the acetabulum after gradual reduction (GR) using traction for developmental dysplasia of the hip (DDH) and the impact on subsequent acetabular development. Methods: A total of 40 patients with DDH (42 hips) undergoing GR using overhead traction and spica casting were retrospectively reviewed. The presence of inverted labrum and the coronal and axial femoral-acetabular distances (FADs) were compared between MRI immediately and five weeks after spica casting. The change in the acetabular index on anteroposterior pelvic radiographs were compared between hips with inverted labrum (residual group) and with normally-shaped labrum (normalized group) on follow-up MRI. Results: The mean age at reduction was 13.1 months (7 to 33) and the mean follow-up duration was 7.7 years (4 to 11). The rate of inverted labrum and the FADs significantly decreased between the MRI scans (all p-values < 0.001), and previous Pavlik harness failure had no negative effect on these decreases. The acetabular indices at the ages of three and five years in the residual group were significantly larger than those in the normalized group (both p-values < 0.001). Residual acetabular dysplasia was seen in 84.2% of the residual group compared with 34.8% of the normalized group (p = 0.002). Conclusion: The docking phenomenon can occur during spica casting following GR using traction in children with DDH between the ages of six months and three years. The remaining inverted labrum at the cast removal may negatively affect subsequent acetabular development. Level of evidence: III - retrospective comparative study